A GNSS Anti-jamming Technology of UAV for Geological Hazard Monitoring - ZHANG Yonggang; ZHOU Chaorong; SHEN Feng (Journal of Harbin University of Science and Technology, 2024)
In this paper,a GNSS anti-jamming technology of UAV for geological hazard survey is designed to realize adaptive interference suppression without vacuum loss under strong jamming environment. This method utilizes the space-time adaptive anti- jamming antenna to process BOC signals, where the steering vector at the frequency corresponding to the two spectral peaks of the BOC signal is extended. The extended steering vector is overlapped as the constraint of the optimal adaptive filtering criterion. Based on which, the optimal weight vector is solved to reduce the loss of BOC signal when the space-time filter suppresses jamming. The simulation results show that the proposed adaptive filtering method based on space-time steering vector extension can not only mitigate the interference, but also protect the energy of BOC signal to the greatest extent and effectively solve the problem of energy loss caused by the traditional filtering algorithm applied to BOC signal.